1995
DOI: 10.2527/1995.73123562x
|View full text |Cite
|
Sign up to set email alerts
|

Energy metabolism in young pigs as affected by mixing.

Abstract: The effect of mixing on energy metabolism was studied in 8-wk-old pigs. In each of two trials, two clusters of 20 pigs (two litters of 10 pigs) were randomly assigned to one of two treatments: control or mixing. Each cluster was housed in two pens. In each trial, after a preliminary period od 2 wk, the two litters within the mixing treatment were mixed at the start of a 2-wk experimental period. During mixing, the five heaviest pigs of each litter were put together in one pen, and the five lightest pigs of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…This response was transient, with no observed differences in duration of feeding behavior in the days following the initial postnursery commingling, except on d 65 after weaning. Similarly, other research has reported that altered or agnostic behaviors were present only during a short time after the commingling stress (McGlone et al, 1987;Heetkamp et al, 1995). We have no explanation, however, for the observations on d 65 after weaning, in which pigs weaned at 21 d of age and mixed, and pigs weaned at 14 d of age and remained unmixed spent a greater percentage of time engaged in feeding behavior.…”
Section: Behavioral Measuresmentioning
confidence: 53%
“…This response was transient, with no observed differences in duration of feeding behavior in the days following the initial postnursery commingling, except on d 65 after weaning. Similarly, other research has reported that altered or agnostic behaviors were present only during a short time after the commingling stress (McGlone et al, 1987;Heetkamp et al, 1995). We have no explanation, however, for the observations on d 65 after weaning, in which pigs weaned at 21 d of age and mixed, and pigs weaned at 14 d of age and remained unmixed spent a greater percentage of time engaged in feeding behavior.…”
Section: Behavioral Measuresmentioning
confidence: 53%
“…Activity-related HP was subsequently calculated (33). The apparent total tract digestibility of nutrients was calculated using acidinsoluble ash as indigestible marker.…”
Section: Methodsmentioning
confidence: 99%
“…Total heat production (H tot ) during the last 6 day of the experimental period was calculated from the gaseous exchanges according to Brouwer's equation (1965). Estimated regression coefficients of H tot and activity counts were used to calculate the heat production related to activity (H act ) as described by Heetkamp et al (1995). The heat production not related to physical activity (H cor ) was calculated by subtracting H act from H tot .…”
Section: Measurementsmentioning
confidence: 99%